New records reveal rapid geographic expansion of Bombus terrestris Linnaeus, 1758 (Hymenoptera: Apidae), an invasive species in Argentina - Benoit Geslin, Mathias Yanin (2015)
Bombus terrestris Linnaeus is an invasive bumblebee in Argentina. Since its first record in March 2006, B. terrestris has rapidly become the most widespread species in the southern Argentina’s Patagonia. The explosion of B. terrestris populations has been associated with the rapid decline of the unique native species B. dahlbomii, Guérin-Méneville. However, B. terrestris had never been yet reported farther south than the 50° parallel. We report for the first time the presence of B. terrestris at the southern end of continental Patagonia and discuss its meaning with regards on potential consequences for B. dahlbomii populations.